Brand Strategies in the Gamer World: A Constant Evolution - Sebastián Morillas, Ana; Martin Soladana, Irene (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
The video game industry, strengthened after the pandemic, has established itself as one of the most dynamic and resilient sectors. In Spain, with over 20 million gamers, the market ranks third in the EU, behind Germany and France. Brands have evolved from traditional advertising to personalized and authentic strategies, including In-game advertising, Advergaming, eSports, influencers, and technologies like the metaverse, adapting to a demanding and diverse consumer base. This analysis highlights how companies are leveraging gaming to stand out in a competitive market, redefining strategies to meet expectations and create meaningful connections with their audience.